Criteria for sport selection of 11-12 year old cyclists - Kolev, I.; Buiuklieva, A. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
For achieving high performance sport results is needed good knowledge and understanding of anatomy and physiology functional characteristics of adolescents, which will help ensuring the use of optimal training methods and help individual sport realization. The establishment of regularities in dynamics of individual indexes, depending on age of young cyclists is of great importance for sport training and sport result prediction as a function of dynamic relation between morphological, motor and technical abilities. The results from the following study may be used to update the training process in cycling by specifying and individualization of training parameters.